Accumulation of coronary risk factors is associated with progression of mitral annular calcification in patients undergoing dialysis therapy: A long-term follow-up study. (15th October 2019) - Usuku, Hiroki; Yamamoto, Eiichiro; Arima, Yuichiro; Takashio, Seiji; Araki, Satoshi; Sueta, Daisuke; Kanazawa, Hisanori; Suzuki, Satoru; Yoshimura, Hiromi; Tsunoda, Ryusuke; Nishigami, Kazuhiro; Uekihara, Soichi; et al.
Abstract: Background: In patients undergoing dialysis therapy, mitral annular calcification (MAC) is a powerful predictor of cardiovascular events and all-cause mortality. However, there is little data on predictors for MAC progression in patients undergoing dialysis therapy. Methods and results: We retrospectively analyzed 98 hemodialysis-dependent patients in Japanese Red Cross Kumamoto Hospital who underwent routine transthoracic echocardiography (TTE) in 2017. Three patients with history of surgical valve replacement or severe valvular heart diseases were excluded. In the 95 enrolled patients, MAC was detected by TTE in 28 patients (29%). A multivariate logistic regression analysis revealed that duration of hemodialysis therapy was independently associated with presence of MAC (odds ratio [OR]: 1.09; 95% confidence interval [CI]: 1.02–1.16; p  < 0.01). Among the 95 patients, 72 patients also underwent routine TTE 5 years previously in 2012. In these patients, progression of MAC from 2012 to 2017 was observed in 11 patients (15%). A multivariate logistic regression analysis revealed that number of coronary risk factors (OR: 2.67; 95% CI: 1.24–5.76; p  = 0.01), baseline MAC diameter (OR: 1.23; 95% CI: 1.05–1.45; p  = 0.01), and left atrial diameter (OR: 0.81; 95% CI: 0.68–0.95; p  = 0.01) were significantly associated with progression of MAC. Conclusions: Accumulation of coronary risk factors was associated with progression of MAC in patients undergoing dialysis. Management of coronary risk factors may be important for inhibition of MAC progression. Highlights: Duration of hemodialysis therapy was associated with the presence of MAC. Accumulation of coronary risk factors was independently associated with progression of MAC, but not with presence of MAC in patients undergoing dialysis. Baseline MAC diameter was also associated with progression of MAC